Solution-processed, fullerene-free organic ultraviolet photodetectors using thermally activated delayed fluorescence materials as electron acceptor. (5th November 2018) - Wang, Xiao; Zhou, Dianli; Wang, Hanyu; Jin, Hui; Yu, Junsheng
Abstract: Solution-processed organic ultraviolet photodetectors (UV-PDs) have been investigated for many years due to their mechanical flexibility and the potential for large-scale roll-to-roll processability. Fullerene derivatives are the most widely used electron acceptors in solution-processed photodetectors. However, they are not suitable for selective UV detection due to their wide absorption spreading the whole visible range. Here, three thermally activated delayed fluorescence (TADF) materials of 4, 5-bis(carbazol-9-yl)-1, 2-dicyanobenzene (2CzPN), 3, 4, 5, 6-tetrakis(carbazol-9-yl)-1, 2-dicyanobenzene (4CzPN) and 2, 4, 5, 6-tetrakis(carbazol-9-yl)-1, 3-dicyanobenzene (4CzIPN) with strong ultraviolet absorption are first utilized as the electron acceptors in solution-processed UV-PDs. Operating at room temperature, all UV-PDs display comparatively photo-detective ability, and the device composed of poly (N-vinyl carbazole) (PVK):4CzPN behaves the best comprehensive performance with a high detectivity of 1.09  ×  10 12 Jones. Additionally, we find that the variations in energy level, film morphology and carrier mobility of the photoactive layer affect the UV-PDs performance, particularly with regards to the dark current and thus the detectivity. By using ultra-thin silver layer as the electrode, visibly semitransparent UV-PDs with an average transmittance of 43% are obtained, and the optical simulations indicate that the light harvest and exciton generation properties of active layers have a strong influence on the performance of the semitransparent devices.